La cognición semántica y sus alteraciones en la demencia y afasia semántica. - Ferrer-Aragón, Jonatan; Patiño-Torrealva, Víctor Manuel (Archivos de Neurociencias, 2018)
Semantic cognition is relatively new topic of interest in neuroscientific research. Its brief history started a few decades ago, from the publication of the first reports on selective impairments of semantic knowledge in brain damaged individuals, and the formulation of the first theoretical models on this topic. In this contribution, we review key issues and hypotheses about the neural organization of semantic cognition, based on a novel framework named Controlled Semantic Cognition, proposed by Lambon Ralph, et. al. We also provide analysis of the main findings supporting this model, obtained from neurofunctional studies in neurologically healthy subjects, as well as neuropsychological studies in patients with semantic dementia and semantic aphasia. This analysis might contribute to a better comprehension of the neurocognitive mechanisms involved in semantic cognition in healthy as well as brain damaged individuals.